A method for selective etching of the metallic bonding phase on the surface of cemented carbide.
The method uses multiple regression analysis to determine corrosion time and depth for cemented carbide tools, addressing complexity and time issues in existing methods, enabling efficient mass production of high-quality tools.
Patent Information
- Application Number
- JP2022066421
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-13
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-04-13
AI Technical Summary
Existing methods for selectively removing the metal binder phase from cemented carbide tools are complex and time-consuming, making it difficult to determine optimal corrosion conditions for different applications, types, and depths, which hinders mass production of high-quality tools.
A method using multiple regression analysis to determine the corrosion time required for a specific depth by considering control variables such as mass ratio, particle diameter, corrosive liquid composition, temperature, flow rate, and vibration, allowing accurate determination of selective corrosion conditions without preliminary experiments.
Enables mass production of high-quality cemented carbide tools that meet customer requirements by determining optimal corrosion depths and times, eliminating the need for individualized preliminary studies.
Smart Images

Figure 0007605491000003 
Figure 0007605491000004 
Figure 0007605491000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for selectively corroding only the metallic bonding phase of a cemented carbide surface by determining a required selective corrosion depth and a corrosion time when selectively corroding only the metallic bonding phase of a cemented carbide surface out of a hard particle phase and a metallic bonding phase contained in the cemented carbide constituting a cemented carbide tool. [Background technology]
[0002] In recent years, Patent Document 1 has reported that the properties of cemented carbide tools used as cutting tools can be improved by removing the metallic binder phase from the tool surface and leaving only the hard particle phase on the surface of the cemented carbide alloy, which is composed of a hard particle phase and a metallic binder phase.
[0003] The metallic bonding phase is removed by chemical etching or physical etching. For example, Patent Document 2 discloses a process for removing the surface metallic bonding phase using aqua regia or nitric acid solution. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2019 / 065677 publication [Patent Document 2] JP 2019-206754 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, it is known that when the metallic bonding phase is selectively removed by chemical etching or physical etching, the surface has improved wear resistance, voltage resistance, lubricity, etc. in a specific usage environment. However, since the depletion depth of the metallic bonding phase is optimal for each type of cemented carbide for each application, such as cutting tools, cutting tools, press tools, drawing dies, and sliding discharge tools, it is difficult to determine the corrosion conditions in advance.
[0006] Conventionally, when the type of cemented carbide and the selective corrosion depth were determined according to customer specifications, a preliminary study of selective corrosion was carried out each time, and the optimal corrosion time was then determined and applied to the product. However, this process was complicated, and it was a major obstacle in terms of quality, cost, and delivery time when customers wanted to mass-produce tools with selectively etched surfaces.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for selectively corroding a metallic bonding phase, which makes it possible to accurately determine selective corrosion conditions, determine a corrosion time required for a target corrosion depth, and selectively corrode a metallic bonding phase contained in a cemented carbide for that corrosion time, without having to carry out preliminary experiments each time for a new application, a new type of cemented carbide, and a new selective corrosion depth. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention provides a method for selectively corroding a metallic bond phase, which selects a required corrosion depth and corrodes only the metallic bond phase on the surface of a cemented carbide out of the hard particle phase and metallic bond phase contained in the cemented carbide constituting a cemented carbide tool, and is characterized in that the influence of control variables that affect the corrosion depth is quantified in advance using multiple regression analysis, the corrosion time required for the target corrosion depth is determined by the multiple regression equation in the multiple regression analysis, and the metallic bond phase contained in the cemented carbide is selectively corroded for that corrosion time.
[0009] In addition, in the present invention, when the corrosion depth is mathematically expressed by multiple regression analysis, the control variables can include at least one of the mass ratio of the hard particle phase to the metallic bond phase, the hard particle diameter of the cemented carbide, the etching solution composition, the etching solution concentration, the etching solution temperature, the corrosion time, the flow rate of the etching solution, and the vibration conditions during corrosion.
[0010] In addition, in the present invention, an optimum corrosion depth for a tool intended for use is determined from the corrosion time obtained by the multiple regression equation, and the corrosion time corresponding to the corrosion depth can be calculated by inputting other control variables.
[0011] This makes it possible to accurately determine the selective corrosion conditions, determine the corrosion time required for the target corrosion depth, and selectively corrode the metallic bonding phase contained in the cemented carbide for that corrosion time without having to perform a preliminary experiment for each new application, new cemented carbide variety, and new selective corrosion depth. Note that the selective corrosion depth is premised on being approximately the same as the average grain size of the hard particles from the viewpoint of strength retention.
[0012] Therefore, for a product application involving new customer requirements, an optimal depth of selective corrosion is determined, and the corrosion time for obtaining this optimal depth is uniquely determined. As a result, product designs that satisfy customer requirements can be determined in the shortest possible time and in the most optimal way without being dependent on individual users, enabling mass production of high-quality cemented carbide tools. Effect of the Invention
[0013] According to the present invention, the optimal depth of selective corrosion is determined for a product application accompanied by new customer requirements, without the need to conduct preliminary experiments for each new application, new type of cemented carbide, and new selective corrosion depth, and the corrosion time for obtaining this optimal depth is uniquely determined. As a result, product designs that satisfy customer requirements are determined in the shortest possible time and in an optimal manner without being dependent on individual factors, and mass production of good quality cemented carbide tools is possible. [Brief description of the drawings]
[0014] [Figure 1]FIG. 1 is a schematic diagram showing a cross section of a cemented carbide tool after selective etching of the metallic bonding phase, and the change in the amount of CO, which is the main component of the metallic bonding phase, during the selective etching. [Diagram 2] FIG. 2 is a diagram for defining the depletion depth of a metallic bonding phase. [Diagram 3] 1 is a flow chart of a method for measuring the depletion depth of a surface metal binder phase in a cemented carbide. [Figure 4] 1 is a flowchart showing a process in which a method for uniquely determining a corrosion time required for a selected corrosion depth is applied to a product manufacturing process. [Diagram 5] 13 is a flowchart for calculating deficiency depth by multiple regression analysis. [Figure 6] FIG. 13 is a diagram showing an example of multiple regression analysis performed on fine grains. [Figure 7] FIG. 13 is a diagram showing an example of multiple regression analysis performed on medium grains. [Figure 8] FIG. 13 is a diagram showing an example of multiple regression analysis performed on coarse particles. [Figure 9] FIG. 13 is a diagram showing details of determining processing conditions for multiple regression analysis. [Figure 10] FIG. 13 is a diagram showing a comparison between a target depletion depth, a calculated depth, and an actually measured depth. [Figure 11] FIG. 1 is a diagram showing the deficiency depth of fine grains actually measured by SEM observation. [Figure 12] FIG. 1 is a diagram showing the deficiency depth of medium grains measured by SEM observation. [Figure 13] FIG. 1 is a diagram showing the deficiency depth of coarse grains actually measured by SEM observation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the method for selectively etching a metallic bonding phase on a surface of a cemented carbide according to the present invention will be described based on an embodiment thereof.
[0016] First, a method for calculating the depletion depth of selective corrosion of a metallic bonding phase, which is the basic technology of the present invention, will be described.
[0017] Figure 1 shows a cross section of the surface of a cemented carbide tool after selective etching of the metallic bonding phase and the C, the main component of the metallic bonding phase. O The graph shows the change in the amount of C in the depleted zone after selective corrosion. O The amount of C does not become completely zero, but fluctuates. From the area where the metallic bonding phase 2 has been removed by corrosion, the amount of C in the unreacted area changes gradually. O A transition in quantity is occurring and the depletion depth needs to be defined in this region.
[0018] Therefore, the inventors assumed a linear change in composition as shown in FIG. 2 and defined the depletion depth of the metallic bonding phase. O The amount is m1, and the small amount of C remaining between the hard particles O Assume that the amount is m2, m2 and m1 are constant values, and the transition from m2 to m1 is a linear change, as shown in Figure 2.
[0019] This linear change occurs at C O The transition position of the amount of Co is defined as the depletion depth d of the metallic bonding phase. Using these definitions, the analysis depth D measured by the X-rays irradiated in the characteristic X-ray analysis, and the amount of Co mx actually measured by the characteristic X-ray analysis, an equation is created based on the conservation of mass of the amount of Co, and the following equation (1) is obtained.
[0020]
number
[0021] By solving equation (1) with respect to the depletion depth d, we obtain equation (2).
[0022]
number
[0023] Here, the concentration of the metallic bonding phase remaining between the hard particles must be estimated in advance using an analysis method attached to the scanning electron microscope, etc. The analysis depth is determined by the X-ray intensity of the characteristic X-ray analyzer used and the composition of the cemented carbide to be analyzed.
[0024] Characteristic X-ray analyzers include energy dispersive X-ray analyzers (EDS) and wavelength dispersive X-ray analyzers (WDS). Both instruments measure the chemical composition of a sample by detecting the characteristic X-rays emitted from the sample surface, with EDS measuring the energy of the characteristic X-rays and WDS measuring the wavelength of the characteristic X-rays.
[0025] In the EDS, the reaction region of the characteristic X-rays is relatively shallow at a depth of several μm, whereas the WDS has an analysis depth of more than 10 μm. In the present invention, considering that the material to be analyzed has hard particles with a diameter of about several μm, it can be said that a wavelength dispersive characteristic X-ray analyzer (WDS), which can measure the depth of multiple particles, is a more desirable analytical device.
[0026] Although the impoverishment depth has such a simplified definition, it is arithmetically uniquely determined and always intersects with the transition region of the Co amount, so it is a very easy definition to handle when stating it as a rule in specifications, etc. In addition, because this measurement method is non-destructive, it can be used directly for shipping inspection and can also be used for cause analysis when an abnormality occurs.
[0027] As described above, it is possible to calculate the depletion depth d of the metallic bonding phase from four pieces of information: the composition m1 of the cemented carbide base body, the composition mx measured from the top surface by characteristic X-ray analysis after the same base body is machined into a tool and the metallic bonding phase is selectively etched, the composition m2 of the metallic bonding phase that remains in small amounts between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth D measured by the emission of characteristic X-rays in characteristic X-ray analysis.
[0028] A flowchart of the above-described method for measuring the depletion depth of the surface metallic binder phase in a cemented carbide is shown in Figure 3. By carrying out this process, the calculated corrosion depth can nondestructively and unambiguously define the depth of the corrosion front, the boundary of which is actually unclear.
[0029] A method for selectively corroding a metallic bonding phase on a surface of a cemented carbide according to an embodiment of the present invention will be described below using the above-mentioned method for calculating the depletion depth of the metallic bonding phase. The present invention relates to a method for determining selective corrosion conditions with high accuracy for a new application, a new type of cemented carbide, or a new selective corrosion depth, without the need to carry out preliminary experiments each time.
[0030] This method is a selective corrosion method for the metallic bonding phase, which is selected when selectively corroding only the metallic bonding phase on the surface of the cemented carbide of the cemented carbide tool from among the hard particle phase and metallic bonding phase contained therein, and which corrodes the metallic bonding phase at the target depth, in which the influence of control variables that affect the corrosion depth is quantified in advance using multiple regression analysis, the corrosion time required for the target corrosion depth is determined by the multiple regression equation in the multiple regression analysis, and the metallic bonding phase contained in the cemented carbide is selectively corroded for that corrosion time.
[0031] When the corrosion depth is expressed as a mathematical expression by multiple regression analysis, the control variables include at least one of the mass ratio of the hard particle phase to the metallic bond phase, the hard particle diameter of the cemented carbide, the etching solution composition, the etching solution concentration, the etching solution temperature, the corrosion time, the flow rate of the etching solution, and the vibration conditions during corrosion. The multiple regression equation is solved for the corrosion time, the optimum corrosion depth for the target tool is determined, and the corrosion time corresponding to the corrosion depth is calculated by inputting the other control variables.
[0032] FIG. 4 shows a flowchart of a process in which the above-mentioned method for uniquely determining the corrosion time required for a selected corrosion depth is applied to a product manufacturing process.
[0033] The following describes the test content and results of the comparison of the target value, the calculated value, and the measured value for the depletion depth d of the metallic bonding phase. FIG. 5 shows a flow chart for calculating the deficiency depth by multiple regression analysis.
[0034] Samples are made using materials with different hard particle diameters and metallic bond phase amounts, and the samples before etching are subjected to component analysis using a wavelength dispersive X-ray analyzer (WDS) or energy dispersive X-ray analyzer (EDS) to identify the amount of metallic bond phase in the parent phase, which is used as the unprocessed calculation standard value. Here, three materials with different particle diameters (fine, medium, and coarse) are targeted, with the average particle diameters of fine grains being 0.6 to 1.0 μm, medium grains being 2.0 to 4.0 μm, and coarse grains being 5.0 μm or more.
[0035] The sample is then etched, and the components of the etched sample are analyzed to identify the amount of metallic bonding phase after etching. From these data and the analysis depth D, the depletion depth of the metallic bonding phase for each sample is calculated using equation (2).
[0036] The samples are classified into material types with different particle sizes, and multiple regression analysis is performed on the depletion depth of the metallic bonding phase to calculate a regression line. From the equation for the regression line, an equation for finding a solution for the treatment time (treatment condition determination equation) is calculated.
[0037] Samples of each material type are produced, and the components of the samples are analyzed before etching to identify the amount of metallic bond phase in the parent phase.The target metallic bond phase depletion depth and processing time are determined using a processing condition determination formula, and etching is performed.
[0038] A specific example in which the above-mentioned processing is carried out will be described below. Figures 6 to 8 show examples of multiple regression analysis for each material type with different particle sizes. Figure 6 shows the regression line for fine grains, Figure 7 shows the regression line for medium grains, and Figure 8 shows the regression line for coarse grains.
[0039] Fig. 9 shows the details of the determination of the processing conditions by this multiple regression analysis, and Fig. 9(a) shows the coefficients in the multiple regression analysis for fine, medium, and coarse grains. Fig. 9(b) shows the calculated processing time obtained by this, and Fig. 9(c) shows the calculated deficiency depth. Note that the processing depth in Fig. 9 is the same as the deficiency depth.
[0040] The target treatment times determined from Fig. 9(c) were 60 seconds for fine grains, 65 seconds for medium grains, and 100 seconds for coarse grains, and the target values of the depletion depth were 0.16 μm for fine grains, 0.76 μm for medium grains, and 1.04 μm for coarse grains. The amount of binder phase was 12.0 wt%, and the treatment solution concentration was 10.0 wt%.
[0041] To compare with this target value, the calculated value of the depletion depth of the metallic bonding phase of the sample was obtained using formula (2), and the actual value of the depletion depth of the metallic bonding phase was measured using a SEM. The cross section of the sample was processed by ion beam milling, and the depth of the depletion of the metallic bonding phase was measured by SEM to perform a depletion depth analysis. The average values were 0.14 μm for fine grains, 0.81 μm for medium grains, and 1.29 μm for coarse grains. Measurements of the depletion depth were performed at several locations, and the average values were used. Figure 11 shows the actual measurement of the depletion depth for fine grains by SEM. Figure 12 shows the actual measurement of the depletion depth for medium grains by SEM. Figure 13 shows the actual measurement of the depletion depth for coarse grains by SEM.
[0042] On the other hand, the calculated depletion depth was 0.14 μm for fine grains, 0.87 μm for medium grains, and 1.32 μm for coarse grains.
[0043] The comparison of the target depletion depth, the calculated depth, and the measured depth is shown in Figure 10. Figure 10(a) is for fine grains, Figure 10(b) is for medium grains, and Figure 10(c) is for coarse grains.
[0044] In Figures 10(a), (b), and (c), the upper and lower limits of the appropriate range of the deficiency depth were determined from the variation in the difference between the regression line value and the plotted analysis data, and Figure 10(d) shows the maximum absolute difference value, the standard deviation σ of the difference, and 3σ. As a result, it was confirmed that in all cases, the values were within the range of ±3σ and did not deviate from the regression line.
[0045] The control variables in the above embodiment are merely examples, and there may be various control variables that affect the corrosion depth. For example, the temperature of the etching solution is a factor that controls the reaction, since it is known that increasing the temperature chemically accelerates the corrosion reaction. In addition, the flow rate of the etching solution is a factor that controls the reaction, since it accelerates the mass transfer of reactive ions in the etching solution and affects the reaction rate. Furthermore, vibration during corrosion is a factor that controls the reaction, since it accelerates the removal of reactants in the gaps of micro recesses and the replenishment of reactive ions, and affects the reaction rate. By using these factors as control variables, varying the levels, and performing multiple regression analysis, the degree of influence can be quantified in the same manner as in the above embodiment.
[0046] In this way, it is possible to perform a similar multiple regression analysis using various control variables that affect the corrosion depth. As control variables for mathematical formulation in multiple regression analysis, the mass ratio of the hard particle phase to the metallic bond phase, the hard particle diameter of the cemented carbide, the etching solution composition, the etching solution concentration, the etching solution temperature, the corrosion time, the flow rate of the etching solution, or the vibration conditions during corrosion can be used.
[0047] By establishing the above-mentioned process, when the optimum depth is determined for a product application with a new customer requirement, the corrosion time required to obtain this optimum depth is uniquely determined. This allows the product design that satisfies the customer requirement to be determined in the shortest and most optimal manner without being dependent on individual skills, enabling mass production of high-quality cemented carbide tools. [Industrial Applicability]
[0048] The present invention can be widely used as a method for selectively corroding a metallic bonding phase, which can accurately determine selective corrosion conditions, determine the corrosion time required for a target corrosion depth, and selectively corrode a metallic bonding phase contained in a cemented carbide for that corrosion time, without having to perform preliminary experiments for each new application, new type of cemented carbide, and new selective corrosion depth. [Explanation of symbols]
[0049] 1 hard particles 2 Metallic bonded phase
Claims
1. A method for selectively corroding only the metallic binder phase on the surface of a cemented carbide tool, comprising: selecting a required corrosion depth; and selectively corroding the metallic binder phase at the target depth, comprising: selecting a control variable that affects the corrosion depth using multiple regression analysis to quantify the degree of influence of the control variable; determining a corrosion time required for the target corrosion depth using a multiple regression equation in the multiple regression analysis; and selectively corroding the metallic binder phase contained in the cemented carbide for the corrosion time; a composition of the metallic bonding phase measured from the top surface by characteristic X-ray analysis after machining the same substrate into a tool and selectively etching the metallic bonding phase; a composition of the metallic bonding phase remaining slightly between hard particles in a depleted region of the selectively etched metallic bonding phase; and an analysis depth measured by emission of characteristic X-rays in characteristic X-ray analysis.
2. 2. The method for selectively corroding a metallic bonding phase on a surface of a cemented carbide according to claim 1, wherein when the corrosion depth is mathematically formulated by multiple regression analysis, the control variables include at least one of a mass ratio of a hard particle phase to a metallic bonding phase, a hard particle diameter of the cemented carbide, a composition of the etching solution, a concentration of the etching solution, a temperature of the etching solution, a corrosion time, a flow rate of the etching solution, and a vibration condition during corrosion.
3. 3. The method for selectively corroding a metallic bonding phase on a surface of a cemented carbide according to claim 1 or 2, characterized in that the multiple regression equation is solved for a corrosion time, an optimum corrosion depth for a target tool is determined, and other control variables are input to calculate a corrosion time corresponding to the corrosion depth.
Citation Information
Patent Citations
Method for photoetching and its equipment
JP1998018057A
Method for manufacturing mold, and mold
JP2010024518A
Surface treatment method of cutting blade tool and cutting blade tool
JP2015182168A
Diamond coated hard metal cutting tool
JP2016087726A
Manufacturing method of slide component
JP2019206754A
